PERANCANGAN SISTEM ELECTRONIC CUSTOMER RELATIONSHIP MANAGEMENT (E-CRM) PADA LAPANGAN FUTSAL - Pandapotan, Handsen (Jurnal Ilmu Komputer dan Sistem Informasi, 2015)
Implementation of business strategies Electronic Customer Relationship Management (e-CRM) in futsal company is to improve the quality from other competitors. Therefore, the purpose this paper is to build a system that can help every member in the transaction as well as shorten the time without having come or contact the company. Kata Kunci: CRM, E-CRM, Fisher Yates Shuffle algorithm, Futsal Sparring, Booking Online